The Effect of Improving Risk Management as a Mediator Variable in the Relationship between the Modern Approach to Internal Auditing and Competitive Advantage: A Study in Yemeni Islamic Banks - Attaf, Wala Farid; Bensbahou, Aziz (International Journal of Economics and Financial Issues, 2025)
This study explores the effect of the risk-based internal audit (RBIA) approach on enhancing competitive advantage in Yemeni Islamic banks, focusing on the mediating role of improved risk management. Conducted on a sample of eight Islamic banks operating in Aden, data was gathered using a structured questionnaire and analyzed with SPSS. The analysis employed linear regression for direct relationships, ANOVA to confirm model significance, and the Baron and Kenny method alongside the Sobel test to examine mediation effects. Findings revealed that the RBIA approach has a statistically significant direct effect on supporting competitive advantage, accounting for 28.3% of the variation. When incorporating improved risk management as a mediating variable, this influence increased to 75%, confirming a partial mediation effect. The study underscores the necessity for Yemeni Islamic banks to fully implement RBIA and align it with risk management practices, particularly in risk identification, assessment, and mitigation. These strategies are critical for strengthening banks’ competitive positioning and resilience in the evolving financial landscape. The study provides actionable insights for Islamic banks in emerging markets, emphasizing the strategic value of integrating advanced auditing approaches with risk management to achieve sustainable growth.